Study on the Optical Properties of High Refractive Index TeO2-PbO-ZnO-BaF2 Glass System - Shiyu Yin; Hao Wang; Aifeng Li; Haoyu Huang; Jing Zhang; Lin Liu; Yuanzhi Zhu (Advances in Materials Science and Engineering)
The tellurite 60TeO2-20PbO-(20-x)ZnO-xBaF2 (x = 1, 3, 5, 6, 7, 9, and 11) series glass samples were prepared. The samples’ SEM, XRD, DSC, density, refractive index, and absorption spectra were tested. A self-made optical platform was used to measure and calibrate the refractive index. The relationship between glass composition and crystallinity was discussed. The effects of density, molar refractive index, and metal standard value on the refractive index of glass samples were studied. The results showed that TPZBF glass has a high refractive index, and the refractive index increases with the increase in BaF2 content.